Association of IL-12B genetic polymorphism with the susceptibility and disease severity of ankylosing spondylitis - Wong, Ruey-Hong; Wei, James Cheng-Chung; Huang, Chun-Huang; Lee, Hong-Shen; Chiou, Shang-Yan; Lin, Shin-Hua; Cai, Yan-Wei; Hung, Pei-Hsuan; Wang, Ming-Fuu; Yang, Shun-Fa (Journal of rheumatology, 2012)
Interleukin 23 (IL-23) stimulates the differentiation of T helper 17 (Th17) cells, which are involved in the pathogenesis of ankylosing spondylitis (AS). Binding of IL-23 to the IL-23 receptor complex activates Janus kinases 2 and tyrosine kinase 2, which phosphorylate IL-23R and subsequently promote the transcription of the IL-17 gene. IL-12B encodes a p40 subunit common to IL-12 and IL-23. We evaluated the effects of IL-12B and IL-23R genotype on the occurrence and clinical features of AS. A total of 362 patients with AS and 362 healthy controls were enrolled in the study. Genotypes of IL-12B A1188C (rs3212227) and IL-23R C2370A (rs10889677) were identified by polymerase chain reaction/restriction fragment-length polymorphism. Disease activity and functional status were assessed by Bath AS indices. Subjects carrying IL-12B CC [matched relative risk (RR(m)) 1.93, 95% CI 1.23-3.03] and IL-12B AC (RR(m) 1.73, 95% CI 1.21-2.46) genotypes had a significantly greater risk of developing AS than subjects with the IL-12B AA genotype. Subjects carrying both IL-12B CC and IL-23R AA genotypes also had a significantly higher risk (RR(m) 2.98, 95% CI 1.51-5.89) of developing AS compared to those with IL-12B AA and IL-23R CC/CA genotypes, and this interaction between IL-12B and IL-23R was significant. Patients with AS who had IL-12B CC and IL-12B AC genotypes had an obviously increased Bath Ankylosing Spondylitis Disease Activity Index score compared to those who carried the IL-12B AA genotype (4.3 vs 3.7). The IL-12B A1188C genotype was associated with the development and disease severity of AS.